Impact of Anxiety, Depression, and Coping Strategies on Health-Related Quality of Life in Patients with Cystic Fibrosis. - KOCAKAYA, DERYA (My University, 2024)
OBJECTIVE: With the significant increase in the life expectancy of cystic fibrosis (CF) patients, many individuals now reach adulthood and develop specific coping strategies to maintain their physical and mental well-being. This study aims to evaluate coping styles and their relationship with mental health and Health-Related Quality of Life (H-RQoL) in adult CF patients. MATERIALS AND METHODS: Thirty adult CF patients completed the Hospital Anxiety and Depression Scale to assess anxiety and depression, the Cystic Fibrosis Questionnaire—Revised to evaluate quality of life, and the Brief Coping Orientation to Problems Experienced questionnaire to assess coping strategies. RESULTS: Twelve individuals (40%) met the diagnostic criteria for being at risk of experiencing anxiety and/or depression. Anxiety risk group exhibited lower life quality scores in the domains of vitality, emotional functioning, and role limitations (P = .027, P = .001, and P = .001, respectively). Patients reporting depressive symptoms had lower scores in emotional functioning and role limitations domains of quality of life (P = .005 and P = .018, respectively). Multivariate analysis indicated that depression and anxiety scores were significant predictors of emotional quality of life. In terms of coping strategies, “acceptance” was the most commonly preferred, while “substance use” was the least preferred strategy among all participants. Patients at risk of anxiety and/or depression often chose “avoidance” as their coping strategy. CONCLUSION: Anxiety and depressive symptoms are prevalent and associated with poorer H-RQoL in adult CF patients. These patients preferred to employ giving up strategy when dealing with the disease. Therefore, it is essential to screen adult CF patients for mental health risks and to work on improving their coping strategies. KEYWORDS: Anxiety, depression, cystic f﻿ibrosis, quality of life, coping
Keywords: Anxiety; depression; cystic f﻿ibrosis; quality of life; coping